Accessibility of Sustainable Beef Cattle Business Development in Mattiro Bulu District, Pinrang Regency - Ilham Rasyid; Indra Wirawan; Sitti Nurani Sirajuddin; Mukhlis Mukhlis (Postgraduate, University of Mataram, 2024)
Beef cattle business development in Alitta Village, Mattiro Bulu Sub-district, Pinrang District, has great potential but also faces a number of challenges. In this context, this study aimed to assess resource accessibility in smallholder beef cattle farming based on the quality of farmers' human resources. Through qualitative methods and literature studies, primary data were obtained from interviews with farmers and business actors, while secondary data were obtained from relevant agencies. The results show that farmer characteristics, such as age, education, experience and training intensity, affect access to financial, technological and physical resources for beef cattle enterprises. Technology integration and innovation, smart marketing, and sustainable environmental maintenance are key strategies in developing this business. By implementing these strategies, Alitta Village can become a model for sustainable beef cattle enterprise development in the surrounding area, providing sustainable economic, social and environmental benefits to the community and surrounding environment